This India - Dhar,Sheila (New Delhi, 1973)
This book describes the developmental efforts of India in the economic, political and sociological spheres since Independence. It is the first reprint with some factual update of a book which was first published to celebrate the 25th anniversary of the Indian Republic. The thrust of the content is Indian culture and the Indian way of life. In this profusely illustrated book traditional motifs from classical, tribal, folk and modern art, familiar to the Indian eye, have been used along with contemporary photographis to project and interpret each theme. The writer, a former senior children, but for general readers also. Her another landmark book for children published by the Division is 'Children's History of India'.
Keywords: Societies India